Multicultural Sweden, assimilationist France: how and why national identity narratives evolve - Blanc-Noël, Nathalie (Sens public)

(untitled) (Département des littératures de langue française, 2010)
This paper examines the differences between Sweden’s and France’s immigration policies the first one beeing multicultural, the other assimilationnist. The hypothesis that will be developed is that such differences can be explained by the political cultures of each country. National identities are based on socially constructed narratives whose contents somehow determine immigration policies basic contents. But a closer examination of Swedish and French immigration policies shows that they are not purely multicultural or assimilationnist. Some adaptations have been made in practice, and the two models tend to become closer.